Modeling the effects of a log export ban in Indonesia - Dudley, R.G. (2004)
Because enforcement of forestry law has become extremely difficult in Indonesia, a ban on export of logs has been suggested as a means of controlling over-harvest and illegal logging. A model of a log export ban can help us visualize its effects on the forestry sector. The model consists of simplified overviews of the wood processing sector, demand - price feedback loops, forest standing stock and log availability, log harvest capacity, and log exports. It examines important feedbacks that must be understood if the potential costs and benefits of a log export ban are to be properly considered. Although some scenarios can help reduce log harvests to sustainable levels, others encourage expansion of small domestic milling capacity leading to increased log harvests. Excess domestic milling capacity added during a log export ban may continue to operate even after a log export ban is lifted. For a log export ban to be an effective tool in combating over-harvest and illegal harvest, limits must also be placed on possible increases in domestic milling and logging capacity.